Implikasi Kebijakan Bebas Visa terhadap Kejahatan Perdagangan Manusia di Indonesia - Baqi, Farul Mudhofarul; Windiani, Reni (Journal of International Relations, 2018)
The Government of Indonesia has issued a free-visa policy (BVKS) for 169 States. Thepolicy is to increase foreign tourist arrivals so as to benefit the economy and tourism ofIndonesia. However, the free –visa policy does not only bring tourists, but also traffickersand victims of human trafficking. This research aims to explain why free-visa policytriggers human trafficking by foreigners in Indonesia. The theoretical framework used ispost-internationalism theory, while the type of research is explanatory. This study showsthat there are three causes for free –visa policy triggering human trafficking crimes inIndonesia, that is : micro factors (increased tourist visits and various motives of foreignersvisiting) ; micro-macro factors (vulnerability of open door immigration policy) and themacro factors (presence of transnational human trafficking crime).